The Design And Implementation Of Backup Server Using The Failover Method - Karneli, Septi; Sapri, Sapri; Akbar, Abdussalam Al (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2024)
One of the most widely used data storage in databases today is using MySQL. MySQL is able to store many data items in it, even up to millions of items. So with so much data in this database, it is very necessary to replicate data to maintain data safety and security. Linux ubuntu server 18.04 is an open source operating system, this operating system is very well used as a server because it does not require high hardware specifications and can also be obtained for free because it is open source. The replication technique is very well applied to the Bengkulu Province Communication and Information Service, this is because the Bengkulu Province Communication and Information Service holds a lot of data. Both internal data and external data. In communicating data to the database using the replication technique, it is very fast with a time of +/- 3 seconds of data communication, this time will also be affected by the condition of the computer network and the device used. The replication technique is very good for agencies that have a very large database and require a long storage time.